2012
DOI: 10.1016/j.rpor.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Exit fluence analysis using portal dosimetry in volumetric modulated arc therapy

Abstract: It is found from this study that the variation due to patient anatomy and interfraction organ motion is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Measuring fluence maps using EPID matirx is one of the standard QA methods in radiotherapy. 13 In-phantom measurements are obtained before the first treatment session. The aim of this method is to compare the calculated (theoretical) fluence maps with the measured (actual) ones.…”
Section: Fig 1 -(A) a Part Of Rtplan Dicom File (B) A Part Of Dynalmentioning
confidence: 99%
“…Measuring fluence maps using EPID matirx is one of the standard QA methods in radiotherapy. 13 In-phantom measurements are obtained before the first treatment session. The aim of this method is to compare the calculated (theoretical) fluence maps with the measured (actual) ones.…”
Section: Fig 1 -(A) a Part Of Rtplan Dicom File (B) A Part Of Dynalmentioning
confidence: 99%
“…This decrease indicates a change in the dose distribution in patients when compared to the first fraction [17]. Morphological changes impact a patient's dose distribution, allowing for an increase in the dose for the organ at risk (OAR) [11,13,[18][19][20]. Increases and decreases in body weight are a form of morphological change [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological changes impact a patient's dose distribution, allowing for an increase in the dose for the organ at risk (OAR) [11,13,[18][19][20]. Increases and decreases in body weight are a form of morphological change [18,19]. Weight loss is a common factor that can occur during radiotherapy [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It converts the pixel data to absolute dose. [8][9][10][11] Several studies of dose-response characteristics have shown that a-Si EPIDs are suitable for dose verification. These studies have shown that the pixel signal is approximately linear with dose and can be converted to absolute dose by measuring the response over a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%